Managing mental health challenges faced by healthcare workers during covid-19 pandemic. (26th March 2020) - Greenberg, Neil; Docherty, Mary; Gnanapragasam, Sam; Wessely, Simon
Abstract : Neil Greenberg and colleagues set out measures that healthcare managers need to put in place to protect the mental health of healthcare staff having to make morally challenging decisions